Inversion Technology Application for Reservoir Characterization in Indonesia - F. Hasan Sidi (Berita Sedimentologi, 2003)
Indonesia has been considered as one of the prolific oil and gas province in the world. In addition to large hydrocarbon reserves already found, including some recent giant fields, there are a wide variety of exploration opportunities awaiting for novel technology or creative minds. Appraisal/development plan is another topic since most of the fields in Indonesia are currently underdeveloped. Modern 3D seismic interpretations coupled with detailed geological understanding has been helping oil companies to improve definition of reservoir geometries and hydrocarbon distribution in several fields. However, that is not always the case since reservoirs most of the time can not be easily visualized through seismic. It will be worse in a production mode as a more detailed understanding of reservoir continuity across the field is a high priority for successful and sustained production.